2019
DOI: 10.1007/s00246-019-02122-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-Extubation Inhaled Nitric Oxide Therapy via High-Flow Nasal Cannula After Fontan Procedure

Abstract: In 2014, our hospital introduced inhaled nitric oxide (iNO) therapy combined with high-flow nasal cannula (HFNC) oxygen therapy after extubation following the Fontan procedure in patients with unstable hemodynamics. We report the benefits of HFNC-iNO therapy in these patients. This was a single-center, retrospective review of 38 patients who underwent the Fontan procedure between January 2010 and June 2016, and required iNO therapy before extubation. The patients were divided into two groups: patients in Epoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Optimal NO therapeutic strategies should be reconsidered to establish an appropriate treatment for PH after mitral valve surgery that will shorten intubation time and length of ICU stay. In the eld of pediatric cardiac surgery, Tominaga et al reported that the duration of postoperative intubation and the length of hospital stay were shorter in patients who received NO inhalation therapy with a high-ow nasal cannula after extubation than in those who did not [14]. The report describes NO inhalation therapy based on the Fontan procedure, in which the use of NO via a high-ow nasal cannula after extubation shortened the tracheal intubation time in half.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal NO therapeutic strategies should be reconsidered to establish an appropriate treatment for PH after mitral valve surgery that will shorten intubation time and length of ICU stay. In the eld of pediatric cardiac surgery, Tominaga et al reported that the duration of postoperative intubation and the length of hospital stay were shorter in patients who received NO inhalation therapy with a high-ow nasal cannula after extubation than in those who did not [14]. The report describes NO inhalation therapy based on the Fontan procedure, in which the use of NO via a high-ow nasal cannula after extubation shortened the tracheal intubation time in half.…”
Section: Discussionmentioning
confidence: 99%
“…34 Further investigation is warranted into the use of iNO with high-flow nasal oxygen therapy, as evidence shows this may reduce the duration of postoperative intubation, pleural draining, and LOS. 35 Sildenafil, a PDE-5 inhibitor and Ambrisentan, a hepatically metabolised endothelin receptor antagonist, can also be used postoperatively to dilate the pulmonary vasculature. Small trials have shown improved haemodynamics, lower use of inotropes, and reduced intubation times with Sildenafil use post-Fontan procedure.…”
Section: Circulationmentioning
confidence: 99%
“…[108][109][110][113][114][115][116] Several smaller studies showed shorter hospital stays with inhaled nitric oxide, although a large retrospective cohort found that inhaled nitric oxide was associated with an increased length of hospital stay. 111,112 Inhaled nitric oxide in combination with other medications may have an additive effect. 117,118 Iloprost is appealing because it can be administered via inhalation; however, studies have shown unfavourable haemodynamics and pulmonary congestion.…”
Section: Pulmonary Vasodilatorsmentioning
confidence: 99%